Perilaku Keuangan Pada Pelaku UMKM Kelurahan Cinere Depok - Harahap, Yosua Triawan; Aziz, Alfida; Cahyani, Dewi (Jurnal Ilmiah Manajemen Kesatuan, 2020)
This research is a quantitative study aimed at knowing the financial literacy, financial attitude, and locus aof control to the financial behavior of SMES in Cinere village. This research uses the SME actors in Cinere village as a population of 30 MSMES. The sample collection is done using a saturated sample means all populations as a sample, so selected 30 respondents from a registered population. Data collected by spreading questionnaires. Data analysis testing is a validity test and reusability test as well as hypothesized analysis in this study using the analysis of PLS (Partial Least Square) with the program smartPLS version 3.0 and a signification rate of 5% (0.05). The results of this study indicated that (1) Financial literacy has no significant effect on financial behavior, (2) Financial attitudes have significant effect on financial behavior, (3) Locus of control significant effect on financial behavior. Keywords: financial literacy, financial attitude, Locus of Control, Financial behavior